The Role of Posyandu Cadres and e-PPGBM Application Operators in Early Detection of Stunting in Kupang City, Nusa Tenggara Timur - Irfan, Irfan; Handayani, Fitri; Pujiyanti, Riny; Artama, Syaputra (Poltekkes Kemenkes Palu, 2024)
Introduction: Data from the 2023 electronic recording and reporting system for community-based nutrition (e-PPGBM) shows a stunting rate of 15,2% in NTT, while the 2022 SSGI data reports a stunting rate of 35,3%. The accuracy of data on stunting cases is critical. To date, the Posyandu (integrated health post) in NTT still relies on manual data recording, which is collected at the Puskesmas (community health centers). The city of Kupang has implemented the e-PPGBM system since 2016, but user acceptance has not been fully assessed due to a lack of studies on the subject. Thus, an evaluation of the knowledge, attitudes, roles and also length of work of Posyandu cadres and the acceptance level of e-PPGBM operators in all Puskesmas in Kupang is necessary. Methods: This study was conducted in 11 Puskesmas in Kupang with 55 Posyandu cadres and 55 e-PPGBM operators as respondents. This study is a mixed- method research. The study used an observational method using questionnaires. System acceptance of e-PPGBM was measured using the HOT (Human-Organization-Technology) model, combined with aspects of regulation and benefits. Qualitative data were collected through in-depth interviews, while secondary data were obtained from e-PPGBM records in the Puskesmas from January to June 2024. Results: The evaluation of the knowledge, attitude, and role of the cadres in early detection of stunting was categorized as good. There was a significant correlation between length of work experience and knowledge (p = 0,036, r=0,036) and the attitude of the cadres (p = 0,034, r=0,054). The system acceptance measurement of e-PPGBM operators was categorized as good in the human aspect, and very good in the organization, technology, knowledge, regulation, and benefit aspects, with correlations found between all variables. Conclusion: Posyandu cadres in Kupang have not yet used the e-PPGBM application, monthly recordings at the Posyandu are still manual, and the application is entirely managed by nutrition officers at the Puskesmas. Limited internet access is a major challenge in using the application. Training is needed to involve cadres in using the application, alongside infrastructure improvements (internet network, PCs, and laptops) at both the Posyandu and Puskesmas levels